PENGARUH FINANCIAL DISTRESS, OPINI AUDIT, PERGANTIAN MANAJEMEN DAN UKURAN KAP TERHADAP AUDITOR SWITCHING (STUDI PADA PERUSAHAAN BUMN YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Muaqilah, Nurul; Mus, Abdul Rahman; Nurwanah, Andi (INVOICE : JURNAL ILMU AKUNTANSI, 2021)
This study aims to analyze and determine the effect of partial financial distress, audit opinion, change of management and size of KAP on auditor switching. This research is a quantitative research type. The object of research is state-owned companies listed on the Indonesia Stock Exchange (IDX) of periode from 2015 to 2019. The Research populations was 25 BUMN componies. The research samples were 8 BUMN companies which fulfilled the criteria with purposive sampling metode Using descriptive statistical techniques and regression analysis assisted by SPSS 26.0  The results of this research show that partially financial distress have a negative and insignificant effect to auditor switching, while audit opinion, change of management and KAP size have a positive and significant effect to auditor switching in BUMN companies listed on the Indonesia Stock Exchange. Keyword : auditor switching, financial distress, audit opinion, change of management, KAP  size